Patterns of failure after postoperative intensity‐modulated radiotherapy for locally advanced buccal cancer: Initial masticator space involvement is the key factor of recurrence. Issue 12 (13th November 2018) - Lin, Yu‐Wei; Chen, Ya‐Fang; Yang, Ching‐Chieh; Ho, Chung‐Han; Wu, Tai‐Ching; Yen, Ching‐Yu; Lin, Li‐Ching; Lee, Steve P.; Lee, Ching‐Chih; Tai, Ming‐Hong
Abstract: Background: The purpose of this study was to determine failure patterns and clinicopathologic prognostic factors in patients with locally advanced buccal cancer after postoperative intensity‐modulated radiotherapy (IMRT). Methods: Eighty‐two patients with locally advanced (American Joint Committee on Cancer [AJCC] stage III/IV) buccal cancer who underwent surgery followed by postoperative IMRT between January 2007 and October 2012 were retrospectively analyzed. Results: Eighteen patients had local recurrences as the first recurrent site and 11 had supramandibular notch recurrences; the majority of recurrences were classified as marginal failures. The median time from the first local or regional recurrence to death was 5.9 months. In multivariate analyses of survivals, the initial masticator space involvement was the most important prognostic factor. Masticator space involvement, N classification, and maxillectomy were the significant prognostic predictors for supramandibular notch recurrences. Conclusion: Postoperative IMRT for buccal cancer should not include the surgical beds alone, rather, it should be based on the potential patterns of spread.